Hybrid Solutions to Cardiac Surgery - Sinclair, Heather Q. (MD Conference Express, 2010)
Until recently, combined coronary artery disease and valvular disease treatments relied customarily on surgical intervention alone. However, traditional surgery is not without its limitations, such as significant morbidity, prolonged hospital stays, neurological complications, sternal wound infections, and high cost. New procedural options have emerged, offering less invasive solutions to cardiac issues with fewer treatment obstacles. Hybrid procedures create a more collaborative treatment environment and may provide improved outcomes and long-term survival benefits compared with traditional surgery.